Inflammatory Cytokines in Diabetic Kidney Disease: Pathophysiologic and Therapeutic Implications - Donate-Correa, Javier; Ferri, Carla M.; Sánchez-Quintana, Fátima; Pérez-Castro, Atteneri; González-Luis, Ainhoa; Martín-Núñez, Ernesto; Mora-Fernández, Carmen; Navarro-González, Juan F. (Frontiers in Medicine, 2021)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease and a main contributing factor for cardiovascular morbidity and mortality in patients with diabetes mellitus. Strategies employed to delay the progression of this pathology focus on the control of traditional risk factors, such as hyperglycemia, and elevated blood pressure. Although the intimate mechanisms involved in the onset and progression of DKD remain incompletely understood, inflammation is currently recognized as one of the main underlying processes. Untangling the mechanisms involved in the appearing of a harmful inflammatory response in the diabetic patient is crucial for the development of new therapeutic strategies. In this review, we focus on the inflammation-related pathogenic mechanisms involved in DKD and in the therapeutic utility of new anti-inflammatory strategies.